Paradigm shift: Online Distance Learning (ODL) / Norhidayah Ali and Azni Syafena Andin Salamat - Ali, Norhidayah; Andin Salamat, Azni Syafena (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2021)
World Health Organization (WHO) has proclaimed the 2019 novel coronavirus disease (COVID-19) as a pandemic. The statistics of infected individuals with COVID-19 has expanded suddenly all over the world. Many countries have announced lockdown and Movement Control Order (MCO) to manage and flatten the curve of the infection. One of the most affected service sectors in Malaysia is the Education Ministry whereby all schools, colleges and universities have been instructed to close for teaching and learning activities. It had taken several months until the government urged all related parties in education to move from the traditional face-to-face teaching to online distance learning (ODL) method.